1990
DOI: 10.1007/bf00764488
|View full text |Cite
|
Sign up to set email alerts
|

The quantum chemical basis of the Fischer-Tropsch reaction

Abstract: Fischer-Tropsch synthesis, transition metal surfaces, CO and CH~ reactivity, electronic features in F-T synthesis, bond strength, activation energy, chemisorption, CO dissociation, extended Hiickel method, ASED method, quantum chemistry.The electronic features determining the reactivity of CO and CH x on transition metal surfaces are reviewed. Focus is on the relevant features that control the Fischer-Tropsch synthesis. The CO dissociation reaction path is controlled by the interaction with the CO bond strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…HREELS [11,12] The authors observed CH formation after exposing the surface to H and heating to 370 K. CH 2 , CH 3 or CH 4 were not observed under UHV conditions. Using theoretical calculations Ciobica et al [5,6] found that CH is the most stable species among all CH x (x=0-4).…”
Section: Energy Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…HREELS [11,12] The authors observed CH formation after exposing the surface to H and heating to 370 K. CH 2 , CH 3 or CH 4 were not observed under UHV conditions. Using theoretical calculations Ciobica et al [5,6] found that CH is the most stable species among all CH x (x=0-4).…”
Section: Energy Calculationsmentioning
confidence: 99%
“…It is believed that a particular form of adsorbed carbon is methanated through a series of hydrogenation reactions of intermediate CH x fragments [2][3][4]. These species adsorbed on various metal surfaces have been studied using, for example, high resolution electron energy loss spectroscopy (HREELS) [7][8][9][11][12][13][14][15], reflection adsorption infrared spectroscopy (RAIRS) [16] and temperature programmed desorption (TPD) [7][8][9]13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of supported Pt metals the dehydrogenation of methane occurs readily, yielding a small amount of ethane in addition to the main products, H 2 , and surface carbon (1)(2)(3)(4)(5)(6)(7)(8). The subsequent hydrogenation of the most reactive carbon gives several higher hydrocarbons and even benzene (1)(2)(3)(4)(5)(6)(7)(8)(9). The formation of the latter compounds has been enhanced by adding Cu metal to Rh/SiO 2 catalyst which was attributed to the migration of CH x species from the Rh onto the Cu, and to the ease of the coupling of CH x fragments on copper surface compared to Rh (9).…”
Section: Introductionmentioning
confidence: 99%
“…A hordozós Pt fémek hatékonyan katalizálják a metán bontását, de a szén lerakódás a katalizátorokon korai dezaktiválódáshoz vezet [39][40][41][42][43][44][45] …”
Section: Szerves Vegyületek Katalitikus Bontása (Metanol Etanol Dmeunclassified